A network of sex and competition: The promiscuous mating system of an invasive weevil. Issue 1 (1st February 2015) - Inghilesi, Alberto Francesco; Mazza, Giuseppe; Cervo, Rita; Cini, Alessandro
Abstract: Invasive alien pest insect species represent a major threat for agriculture and biodiversity. Because chemical treatments employed to contrast such pests elicit serious environmental and human health problems, a great effort is currently directed to develop long term and environmentally friendly biological control strategies. However, the successful application of some promising techniques, such as the Sterile Insect Technique (SIT), requires a deep knowledge of the pest basic biology. Here, we argue that understanding pest sexual biology using a social network approach can significantly improve the performance of control strategies. For example, SIT may benefit from understanding how individuals interact and how males accede to reproduction, in order to target the most reproductively active and polygamic males. In this paper we studied the socio-sexual networks of the Asian red palm weevil (RPW) Rhynchophorus ferrugineus, a worldwide invader which is causing heavy economic impacts on several palm species. We found that the RPW has a highly promiscuous mating system, characterized by forced interruptions of pair copulations by additional males. The social network is highly non-random nor regular: few males almost monopolize reproduction, behaving as key-players in the network of matings. Additionally, males have a stable pattern of sexual behaviour over time. We use RPW social network as a case study to direct the development of management techniques such as SIT strategy.